Pendampingan Pelajaran Tarikh Islam Melalui Youtube Tentang Nabi Muhammad SAW di Thawalib Padang - Muthia Azizah; Martin Kustati; Rezki Amelia (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The purpose of mentoring students in Islamic Date lessons through youtube learning media about the prophet's sirah nabawiyah Prophet Muhammad SAW at Ponpes Thawalib Padang so that students better understand and remember more about the prophet Muhammad's sirah nabawiyah. By using youtube as a learning medium, students are more interested in listening and paying attention in carrying out the learning process. This assistance is carried out using the first stage of Participatory Action Research (PAR) method, conducting questions and answers or reviewing students' memories of the Prophet Muhammad SAW what students previously knew before watching youtube, then watching youtube sirah nabawiyah about the Prophet Muhammad SAW, then conducting discussions or questions and answers with students asking things related to what they have watched Finally, draw conclusions from what they have watched, which is asked from one of the students or several students to draw conclusions, then concluded more clearly by the teacher so that the students understand more about the Prophet Muhammad SAW. As for the results of the assistance that has been carried out in the first stage, there is a response given by the students to the questions given about the understanding of students who previously knew about the Prophet Muhammad SAW, After watching the youtube sirah nabawiyah about Prophet Muhammad SAW, students and teachers had a discussion about what had been watched so that questions arose given by students to what they had understood. Finally, make conclusions about the Prophet Muhammad SAW through watching YouTube that has been watched with students. By using YouTube, students are more interested in knowing the nabawiyah sirah about the Prophet Muhammad SAW.